2012
DOI: 10.1007/s00359-012-0718-1
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic signal perception in a noisy habitat: lessons from synchronising insects

Abstract: Acoustically communicating animals often have to cope with ambient noise that has the potential to interfere with the perception of conspecific signals. Here we use the synchronous display of mating signals in males of the tropical katydid Mecopoda elongata in order to assess the influence of nocturnal rainforest noise on signal perception. Loud background noise may disturb chorus synchrony either by masking the signals of males or by interaction of noisy events with the song oscillator.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…We simulated the active space of synchronous signallers by means of a two-dimensional multi-agent computer model that was developed in Netlogo (v. 5.0). Simulations of the active space are based on realistic sound propagation properties observed in the field [ 35 ] and take into account the hearing threshold of receivers, which was set to either 40 or 50 dB SPL, whereby a hearing threshold of 40 dB SPL roughly corresponds to silent laboratory conditions [ 38 , 39 ]. Mecopoda choruses have been recorded in the field exclusively in rainforest clearings where variation in the third dimension was small (M. Hartbauer 2012, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…We simulated the active space of synchronous signallers by means of a two-dimensional multi-agent computer model that was developed in Netlogo (v. 5.0). Simulations of the active space are based on realistic sound propagation properties observed in the field [ 35 ] and take into account the hearing threshold of receivers, which was set to either 40 or 50 dB SPL, whereby a hearing threshold of 40 dB SPL roughly corresponds to silent laboratory conditions [ 38 , 39 ]. Mecopoda choruses have been recorded in the field exclusively in rainforest clearings where variation in the third dimension was small (M. Hartbauer 2012, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…Römer et al [38] found modifications to the temporal calling patterns in two sympatric katydid species, Hemisaga dendiculata and Mygalopsis marki, that almost completely overlap in call frequency, with H. dendiculata song suppressed in the presence of calling M. marki. In another species, Mecopoda elongata, which sings in choruses, levels of synchrony were reduced with increasing nocturnal rainforest noise [39]. Background noise can also induce changes in phonotaxis (the ability to move in an orientation with respect to a sound source).…”
Section: (B) Evidence For Changes In Response To Noisementioning
confidence: 99%
“…Indeed recent studies suggest that the concept can be applied to complex behavioural phenotypes, for example sociality, which is multifaceted and has several phylogenetic origins (Fischman, Woodard, & Robinson, 2011; Toth & Robinson, 2009; Toth et al, 2007). Behavioural ecologists have uncovered a surprising diversity of complex phenotypes that have arisen repeatedly across taxa, for example, reproductive strategies like male chorusing and female-mimicking male sneaking behaviours, and foraging behaviours like echolocation (Hanlon, Naud, Shaw, & Havenhand, 2005; Hartbauer, Siegert, Fertschai, & Romer, 2012; Jordão, Fonseca, Amorim, & Janik, 2012; Parker et al, 2013; Taborsky, 2008). A genomic approach could begin to address whether shared mechanisms, in addition to ecological factors, are in part responsible for this type of convergence (Arendt & Reznick, 2008).…”
Section: Identifying Genetic Toolkits For Behaviourmentioning
confidence: 99%